2006
DOI: 10.1097/01.iae.0000254895.78766.af
|View full text |Cite
|
Sign up to set email alerts
|

Photic Retinopathy After Cataract Surgery in Diabetic Patients

Abstract: Diabetic patients may be more vulnerable to photic injury. Surgeons should take precautions to prevent PR when performing cataract surgery on diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Increases in the duration and complexity of phacoemulsification surgery have been identified as important risk factors for DR progression and subsequent visual compromise [421]. Diabetic patients may also be more vulnerable to photic retinopathy, and intraoperative precautions such as reducing operating time with a senior surgeon should be considered to minimise this risk [432].…”
Section: Intra-operativementioning
confidence: 99%
“…Increases in the duration and complexity of phacoemulsification surgery have been identified as important risk factors for DR progression and subsequent visual compromise [421]. Diabetic patients may also be more vulnerable to photic retinopathy, and intraoperative precautions such as reducing operating time with a senior surgeon should be considered to minimise this risk [432].…”
Section: Intra-operativementioning
confidence: 99%
“…[ 65 ] Cetinkaya et al . [ 66 ] showed that photic retinopathy during cataract surgery was more prevalent in diabetic patients than nondiabetics. The mere presence of diabetes does not increase the risk of intraoperative complications such as posterior capsular rupture, zonular dehiscence, and vitreous loss.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with NVI, bleeding in the anterior chamber during or after surgery should also be kept in mind. Photic retinopathy during cataract surgery, especially surgeries of a longer duration, was also more prevalent in diabetic patients than nondiabetics[66].…”
Section: Cataract Surgery In Diabetic Patientsmentioning
confidence: 99%